IMPLEMENTASI KEBIJAKAN PENANGGULANGAN HIV DAN AIDS DI JAWA TENGAH (KAJIAN PERATURAN DAERAH PROVINSI JAWA TENGAH NOMOR 5 TAHUN 2009) - Afriani Hanna Sagala; Sri Suwitri; Slamet Santoso (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
HIV and AIDS policy in Central Java was an attempt by the provincial government of Central Java to tackling HIV and AIDS in Central Java. The developments of HIV and AIDS cases are quite high in the Central Java provincial government make management efforts in solving this disease. Efforts were made consisting of prevention, treatment effort, and rehabilitation effort. On the implementation of the policy implementation of HIV and AIDS in Central Java, there are several factors that affect implementation.This study aimed to describe the process of implementation of HIV and AIDS policies has done by the provincial government of Central Java and to describe the factors that influence policy implementation. This study uses a descriptive qualitative method. Data collection methods used were in-depth interviews and documentation techniques.The finally about HIV and AIDS solve up implementation on central of Java there aren’t optimal away from this solved. That looks at for a few exactly of implementation that not yet doing optimally. The factors that’s under of implementation, for example communication, human resources development, the nature of conditions, and disposition is not better.